2019
DOI: 10.3390/ijerph16122131
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Mobile App for Accessible Beach Tourism Information for People with Disabilities

Abstract: The global increase in the proportion of the population with disabilities has caused a greater awareness toward guaranteeing their use of public services. In particular, there is emphasis on the accessibility and inclusivity of tourism resources, to improve the enjoyment and well-being for people with motor disabilities. This paper presents a case study on accessibility to beaches in the Region of Murcia, Spain, which is one of the main tourist areas in the country. First, the most important elements that allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 15 publications
3
22
1
Order By: Relevance
“…Previous research related to accessibility and tourism includes studies based on the importance of this segment within the tourism sector market [6][7][8][9], as well as those focused on the digital analysis of websites or apps in the tourism sector [10][11][12]. However, no studies were found that evaluated both the apps and websites of the same institution or company, whether public or private.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research related to accessibility and tourism includes studies based on the importance of this segment within the tourism sector market [6][7][8][9], as well as those focused on the digital analysis of websites or apps in the tourism sector [10][11][12]. However, no studies were found that evaluated both the apps and websites of the same institution or company, whether public or private.…”
Section: Introductionmentioning
confidence: 99%
“…The future agenda of the accessible tourism market must take into account different influencing factors if it is to achieve adequate progress. Some of the advances required are as follows: the need to provide sources of accessible information that increase the participation of PwD in the various tourist activities [63], review of compliance with policies and regulations that determine how well PwD can access online tourist information [64], and identify ways of using new and emerging technologies that allow for enhancing value co-creation by providing the opinion of tourists with disabilities on accessibility to different tourist environments [65].…”
Section: Accessible Tourism As An Emerging Market Betmentioning
confidence: 99%
“…For example, When Chick-fil-A, one of the largest American fast food restaurant chains, released its first official app, it reached first place in the app store in only 3 days after it was launched. Mayordomo-Martínez et al (2019) note that these apps are popular for four main reasons. Firstly, customers feel that no one is waiting in line or getting put on hold.…”
Section: Technological Naturementioning
confidence: 99%